Edukasi tentang Pengetahuan dan Sikap Remaja terhadap Penyalahgunaan NAPZA pada Siswa SMP Al-Amanah Tahun 2025 - Abul A’la Al Maududi; Niswatun Najihah; Nurala Rahma Wardian; Ridha Elhanina Ramadhini; Muhammad Sopyan Atsaury; Almira Chiara Putri Nusantara; Anis Hilmi Dwi Syafitri; Siti Naila Syabani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Substance abuse of Narcotics, Psychotropics, and Addictive Substances (NAPZA) is a significant public health issue, particularly among adolescents. The lack of knowledge about the effects and prevention of NAPZA is one of the risk factors for its abuse. Therefore, this activity aims to increase adolescents' knowledge about preventing NAPZA abuse through health education. The activity was conducted on December 11, 2025, at SMP Al-Amanah, South Tangerang City, involving 59 students. The method used was health counseling accompanied by interactive discussions. Evaluation was carried out using pre-test and post-test to measure the participants' knowledge improvement. The results of this activity showed a significant increase in students' knowledge, as reflected in the higher post-test scores compared to the pre-test. Health education proved to be effective in enhancing adolescents' understanding of the dangers of NAPZA abuse and how to prevent it. Thus, this activity can serve as an initial step in reducing NAPZA abuse rates among adolescents, which is crucial for supporting their mental and physical health. Ongoing education is expected to strengthen adolescents' awareness of the importance of protecting themselves from NAPZA abuse.